Translation in the Context of EFL - The Fifth Macroskill? - Stuart Campbell (TEFLIN, 2003)
EFL teaching methods often ignore the first language altogether and as a consequence ignore the potential of translation in language learning. Four factors that undermine the lack on integration of translation and EFL are 1) a strong anti-translation bias in EFL teaching methodology; 2) lack of recognition of translation in EFL publishing industry; 3) obstacles stemming from the demographics of EFL; 4) lack of interest from translation scholars. This paper argues that there are advantages of incorporating translation into ESL teaching.